Peripheral immune profiling of soft tissue sarcoma: perspectives for disease monitoring - Almeida, Jani Sofia; Sousa, Luana Madalena; Couceiro, Patrícia; Andrade, Tânia Fortes; Alves, Vera; Martinho, António; Rodrigues, Joana; Fonseca, Ruben; Freitas-Tavares, Paulo; Santos-Rosa, Manuel; Casanova, José Manuel; Rodrigues-Santos, Paulo (Frontiers in Immunology, 2024)
Studying the tumor microenvironment and surrounding lymph nodes is the main focus of current immunological research on soft tissue sarcomas (STS). However, due to the restricted opportunity to examine tumor samples, alternative approaches are required to evaluate immune responses in non-surgical patients. Therefore, the purpose of this study was to evaluate the peripheral immune profile of STS patients, characterize patients accordingly and explore the impact of peripheral immunotypes on patient survival. Blood samples were collected from 55 STS patients and age-matched healthy donors (HD) controls. Deep immunophenotyping and gene expression analysis of whole blood was analyzed using multiparametric flow cytometry and real-time RT-qPCR, respectively. Using xMAP technology, proteomic analysis was also carried out on plasma samples. Unsupervised clustering analysis was used to classify patients based on their immune profiles to further analyze the impact of peripheral immunotypes on patient survival. Significant differences were found between STS patients and HD controls. It was found a contraction of B cells and CD4 T cells compartment, along with decreased expression levels of ICOSLG and CD40LG; a major contribution of suppressor factors, as increased frequency of M-MDSC and memory Tregs, increased expression levels of ARG1, and increased plasma levels of IL-10, soluble VISTA and soluble TIMD-4; and a compromised cytotoxic potential associated with NK and CD8 T cells, namely decreased frequency of CD56 dim NK cells, and decreased levels of PRF1, GZMB, and KLRK1. In addition, the patients were classified into three peripheral immunotype groups: "immune-high," "immuneintermediate," and "immune-low." Furthermore, it was found a correlation between these immunotypes and patient survival. Patients classified as "immune-high" exhibited higher levels of immune-related factors linked to cytotoxic/effector activity and longer survival times, whereas patients classified as "immune-low" displayed higher levels of immune factors associated with immunosuppression and shorter survival times. In conclusion, it can be suggested that STS patients have a compromised systemic immunity, and the correlation between immunotypes and survival emphasizes the importance of studying peripheral blood samples in STS. Assessing the peripheral immune response holds promise as a useful method for monitoring and forecasting outcomes in STS.